Ceding Control: An Experimental Analysis of Participatory Management - Philip Mellizo; Jeffrey P. Carpenter; Peter Hans Matthews (Institute of Labor Economics (IZA), 2017)
We use an experiment to evaluate the effects of participatory management on firm performance. Participants are randomly assigned roles as managers or workers in firms that generate output via real effort. To identify the causal effect of participation on effort, workers are exogenously assigned to one of two treatments: one in which the manager implements a compensation scheme unilaterally or another in which the manager cedes control over compensation to the workers who vote to implement a scheme. We find that output is between seven and twelve percentage points higher in participatory firms.
Keywords: C92; J33; J53; J54; M50; 330; voice; control; intrinsic motivation; participatory management; real effort; experiment